The Impact of Emotional Intelligence on Prosocial Behavior among High School Students: A Correlational Study: Dampak Kecerdasan Emosional terhadap Perilaku Prososial di Kalangan Siswa Sekolah Menengah Atas: Sebuah Studi Korelasional - Artono, Henry Dwi; Mariyati, Lely Ika (Indonesian Journal of Education Methods Development, 2023)
This study aimed to examine the relationship between emotional intelligence and prosocial behavior among students at SMA Negeri 1 Taman. A quantitative correlational approach was employed, with a sample of 290 students selected using stratified random sampling from the total population of 1,118 students. Data collection involved psychological scales, and Spearman's rho was used for data analysis. The results revealed a significant correlation (p < 0.05) between emotional intelligence and prosocial behavior among the students, with a correlation coefficient of 0.951, indicating a strong positive correlation. The majority of students demonstrated high levels of both emotional intelligence (57.6%) and prosocial behavior (60.3%). These findings suggest that an increase in emotional intelligence positively influences prosocial behavior, while a decrease in emotional intelligence leads to a decline in prosocial behavior. The implications of this research provide a basis for understanding students' emotional intelligence and prosocial behavior levels, allowing for interventions to enhance emotional intelligence and maximize prosocial behavior. Future studies should consider increasing the sample size and exploring additional factors, such as mood, genetic factors, situational influences, and personality, which may impact prosocial behavior. Highlight: Significant correlation: The study establishes a significant correlation between emotional intelligence and prosocial behavior among high school students, indicating a strong positive relationship. Impact of emotional intelligence: Higher levels of emotional intelligence contribute to an increase in prosocial behavior, while a decrease in emotional intelligence leads to a decline in prosocial behavior. Implications for intervention: The findings provide a basis for developing interventions to enhance students' emotional intelligence and maximize their prosocial behavior. Strategies such as organizing study groups and fostering empathy towards the environment can be implemented to improve emotional intelligence. keyword: Emotional Intelligence, Prosocial Behavior, High School Students, Correlation, Quantitative Study